EFEKTIFITAS PENGGUNAAN MODUL MATEMATIKA DASAR PADA MATERI BILANGAN TERHADAP HASIL BELAJAR - Rahma Ramadhani; Abdiyah Amudi (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This study aims to determine the effectiveness of the use of basic mathematic modules based on contextual at the chapter of numbers. The research object were 30 students who took basic mathematics courses. The research method used is a quantitative method and use One Group Pretest-Posttest Design. Tests performed are n-gain, normality test, homogeneity test and T-test (Paired Sample T-Test). The results showed that the effectiveness of using the n-gain calculation module was 0.61 categorized as moderate. The normality test with Kolmogorov-Sminorv showed significant 0.200 (pretest), 0.092 (posttest), 0.200 (gain), and 0.200 (n-gain) which showed normal distribution. Homogeneity test with Lavene test showed the average significance of 0.98 > 0.05 (homogeneous). The average grade before and after the use of the module increased from 61.13 to 85.13 with the Paired Sample T-Test obtained a significance level of 0.00, <0.05 (effective). The result show that the provision of contextual basic mathematics modules of chapter of number effectively improves student learning outcomes with the category of